THE INFLUENCE OF TAX AVOIDANCE, TUNNELING INCENTIVES AND BONUS MECHANISM ON TRANSFER PRICING WITH LEVERAGE AS A MODERATION VARIABLE - Zuliana, Erlin; Soerono, Ayu Noorida; Tjahjono, Mazda Eko Sri (Review of Accounting and Taxation, 2024)
Purpose – This research aims to determine the effect of tax avoidance, tunneling incentives, and bonus mechanisms on transfer pricing with Leverage as a moderating variable in manufacturing companies in the consumer goods industry sector, which is listed on the Indonesia Stock Exchange in 2016-2021Design/methodology/approach—Purposive sampling was used for sample selection, and 13 companies were selected for a total of 51 research data. Multiple linear regression and MRA were used for analysis with SPSS version 25 software. Finding - The results of this study indicate that tax avoidance has a significant positive effect, and tunneling incentives and bonus mechanisms have a significant negative effect on transfer pricing. Meanwhile, Leverage cannot weaken the impact of tax avoidance, tunneling incentives, and bonus mechanisms on transfer pricing.Originality - The originality of this research is to include a moderating variable, namely Leverage.Keywords - Tax Avoidance, Tunneling Incentive, Bonus Mechanism, Transfer Pricing, Leverage